The Integration of Local Muslim Culture in Islamic Education: Adaptation and Negotiation within Madrasahs in Indonesia and Southern Thailand - Mohammad Faruq; Sauqi Futaqi; Zuli Dwi Rahmawati; Busainah Mateh (Journal of Contemporary Islamic Education, 2026)
This study addresses the growing challenge faced by Islamic education in plural societies, where tensions often arise between normative religious teachings and diverse local cultural practices. In contexts such as Indonesia and Southern Thailand, madrasahs are required to navigate these tensions while maintaining both religious authenticity and social relevance. This study examines how local Muslim culture is integrated into Islamic education through processes of adaptation and negotiation, and how these processes contribute to the construction of contextual religious identities. A qualitative comparative case study design was employed, with data collected through in-depth interviews, classroom observations, and document analysis in two madrasahs representing different socio-cultural settings. Data were analyzed using thematic coding and cross-case comparison. The findings reveal that cultural integration functions as an active pedagogical and sociocultural process rather than mere value transmission. Local traditions—such as communal religious rituals, language practices, and historically embedded narratives—are systematically incorporated into learning through curriculum adaptation, extracurricular activities, and community engagement. These practices not only enhance students’ cultural awareness and inclusivity but also strengthen the internalization of Islamic values in contextually meaningful ways. Furthermore, adaptation and negotiation serve as mechanisms to mediate tensions between religious norms and lived cultural realities. Although limited to two institutions, this study contributes to the discourse on multicultural Islamic education by offering a comparative and context-sensitive perspective for curriculum development in diverse Muslim societies.